Designing an Online Discussion Strategy with Learning Analytics Feedback on the Level of Cognitive Presence and Student Interaction in an Online Learning Community - Alwafi, Enas (Online Learning, 2022)
This study investigated the impact of using a discussion strategy with learning analytics on the level of student cognitive presence and interaction. The study used a quasi-experimental design with control and experimental groups. The experimental group applied open-ended discussion and elaborated feedback with learning analytics while the control group applied open-ended discussion and elaborated feedback without learning analytics. A mixed-method approach was used in this study. Data were collected through content analysis, social network analysis (SNA), and interviews. The results showed that the level of cognitive presence in the experimental group increased more than the control group. SNA revealed that students in the experimental group developed more cognitive learning ties with their peers during the process of developing cognitive presence. Interview data showed that students found that the discussion strategy with learning analytics made them aware of their level and quality of interaction and their role in building knowledge in an online learning community. In addition, they felt that the discussion strategy with learning analytics increased their motivation to participate in the discussion. This study provides recommendations on how students can enhance their cognitive presence and learning experience in an online learning community.